Borderzone Departure Cities: Jumping‐Off Urbanism of Irregular Migration on the Edges of Europe - Katz, Irit (Wiley, 2023)
Abstract The increasing fortification of borders produces new urban forms of irregular migration. This paper invokes the concept of “borderzone departure cities” as urban constellations created where global migration routes meet blocked borders in cities which become jumping‐off points from which migrants try to depart. The paper examines Athens and Calais as borderzone departure cities located at both sides of the EU Schengen area. By focussing on the Athenian City Plaza squat and the makeshift Calais Jungle camp as emblematic yet relational spaces of departure, the paper moves beyond the squat/camp divide to better understand how irregular migrants struggle against hostile bordering apparatuses through urban practices of meanwhile inhabitation and mobile commoning. The paper illustrates how these spaces were variously assembled, run, and experienced to form the conditions for movement and stay, each holding different potentials for creating solidarity infrastructures and negotiating forms of migrant citizenship to support the uncertain urban realities of those stuck on the move.
Keywords: 44 Human Society; 4406 Human Geography; 4403 Demography